(untitled) (Journal of the Management Sciences, 2023)
The objective of this study is to explore the nexus of book tax aggressiveness and corporate social responsibility of quoted consumer goods manufacturing firms on the Nigerian Stock Exchange (NSE). The study adopted the ex post facto research design. The population is comprised of quoted consumer goods manufacturing firms on the Nigerian Stock Exchange. The sample was purposively delimited to twenty-one firms in the consumer goods manufacturing sector. The study relied on secondary sources of data retrieved from the published annual reports of the respective companies from 2011 to 2019. The data were analysed using both descriptive and inferential statistical techniques. The hypotheses were analysed using multiple regression; specifically the Fixed Effects Model (FEM) technique. The results showed that the temporary and permanent book-tax differences had a negative non-significant relationship with the corporate social responsibility of quoted consumer goods firms. Based on these, the study recommends among others that policymakers and regulatory bodies should formulate policies that strike a balance between enhancing CSR and tax payments; this would safeguard firms’ investors from manipulative tax practices with their potential negative effect on firm valuation and promote societal development.